An intermedia synchronisation mechanism for multimedia distributed systems. (24th September 2009) - Pomares Hernandez, S.E.; Estudillo Ramirez, J.; Morales Rosales, L.A.; Rodriguez Gomez, G.
Distributed Multimedia Systems (DMS) deal with simultaneous geographically distributed sources by transmitting heterogeneous data. The preservation of temporal relations among different data types and simultaneous distributed sources is an open research area. This paper proposes a temporal synchronisation mechanism to be used at runtime in a DMS. One original aspect is that the present work avoids the use of a common reference by executing all multimedia temporal relations according to their causal dependencies. The mechanism is emulated considering a WAN environment and using MPEG-4 encoders. The results show that our mechanism is effective in reducing the intermedia synchronisation error.